Myokine myostatin is a novel predictor of one-year radiographic progression in patients with rheumatoid arthritis: A prospective cohort study - Lin, Jian-Zi; Ma, Jian-Da; Yang, Li-Juan; Zou, Yao-Wei; Zhang, Xue-Pei; Pan, Jie; Li, Qian-Hua; Li, Hong-Gui; Yang, Ze-Hong; Wu, Tao; Zhang, Qian; Mo, Ying-Qian; et al. (Frontiers in Immunology, 2022)
Background: Associations between rheumatoid arthritis (RA) and reduced skeletal muscle have been studied, and we firstly reported myopenia independently predict one-year radiographic progression in RA. Myokine myostatin can negatively regulate skeletal muscle mass and promote osteoclast differentiation. However, there is no report about their relationships in RA patients. We firstly explored the relationship of serum myostatin and disease characteristics, as well as aggravated joint destruction during one-year follow-up. Methods: Consecutive RA patients were recruited from a real-world prospective cohort and completed at least one-year follow-up. Baseline serum level of myostatin was measured by enzyme-linked immunosorbent assay. Clinical data in RA patients as well as muscle index in both RA patients and healthy controls were collected. One-year radiographic progression as primary outcome was defined by a change in the total Sharp/van der Heijde modified score ≥0.5 units. Results: Totally 344 RA patients (age 47.9±12.5 years, 84.0% female) and 118 healthy control subjects (age 42.8±11.3 years, 74.6% female) were recruited. Compared with healthy controls, RA patients showed a higher level of serum myostatin at baseline (3.241±1.679 ng/ml vs. 1.717±0.872 ng/ml, P<0.001), although lower ASMI (6.0±0.9 kg/m2 vs. 6.5±1.0 kg/m2, P<0.001). In RA patients, those with high myostatin level showed a higher rate of radiographic progression than low myostatin group (45.3% vs. 18.6%, P<0.001). Furtherly, RA patients were stratified into four subgroups according to serum myostatin and myopenia. Compared with other three subgroups, RA patients with high myostatin overlapping myopenia had the highest rate of radiographic progression (67.2% vs. 10.3%-31.4%, P<0.001), as well as the lowest proportion of remission and the highest rate of physical dysfunction during one-year follow-up. After adjustment for confounding factors, high serum myostatin (AOR=3.451, 95%CI: 2.016-5.905) and myopenia (AOR=2.387, 95%CI: 1.416-4.022) at baseline were risk factors for one-year radiographic progression, especially for those with high myostatin overlapping myopenia (AOR=10.425, 95%CI: 3.959-27.450) as the highest-risk individuals among four subgroups. Significant synergistic interaction effect was observed between high myostatin and myopenia on one-year radiographic progression (AP=66.3%, 95%CI: 43.2%-89.3%). Conclusion: Myostatin is a novel predictor of aggravated joint destruction in RA patients which has synergistic interaction with myopenia for predicting value.